Effect of smoking cessation on quantitative computed tomography in smokers at risk in a lung cancer screening population - Jobst, Bertram; Weinheimer, Oliver; Trauth, Mila; Becker, Nikolaus; Tremper, Jan; Delorme, Stefan; Eichinger, Monika; Kauczor, Hans-Ulrich; Wielpütz, Mark Oliver (European radiology, 2018)
Objective To longitudinally evaluate effects of smoking cessation on quantitative CT in a lung cancer screening cohort of heavy smokers over 4 years.Methods After 4 years, low-dose chest CT was available for 314 long-term ex-smokers (ES), 404 continuous smokers (CS) and 39 recent quitters (RQ) who quitted smoking within 2 years after baseline CT. CT acquired at baseline and after 3 and 4 years was subjected to well-evaluated densitometry software, computing mean lung density (MLD) and 15th percentile of the lung density histogram (15TH).ResultsAt baseline, active smokers showed significantly higher MLD and 15TH (-822±35 and -936±25 HU, respectively) compared to ES (-831±31 and -947±22 HU, p<0.01-0.001). After 3 years, CS again had significantly higher MLD and 15TH (-801±29 and -896±23 HU) than ES (-808±27 and -906±20 HU, p<0.01-0.001) but also RQ (-813±20 and -909±15 HU, p<0.05-0.001). Quantitative CT parameters did not change significantly after 4 years. Importantly, smoking status independently predicted MLD at baseline and year 3 (p<0.001) in multivariate analysis.ConclusionOn quantitative CT, lung density is higher in active smokers than ex-smokers, and sustainably decreases after smoking cessation, reflecting smoking-induced inflammation. Interpretations of quantitative CT data within clinical trials should consider smoking status. Key Points • Lung density is higher in active smokers than ex-smokers. • Lung density sustainably decreases after smoking cessation. • Impact of smoking cessation on lung density is independent of potentially confounding factors. • Smoke-induced pulmonary inflammation and particle deposition influence lung density on CT.
Gesehen am 29.08.2018